Upcycling of plastic waste in bituminous mixes using dry process: Review of laboratory to field performance - Singh A.; Gupta A. (My University, 2025)
This paper comprehensively reviews present research on the potential for repurposing primary categories of waste plastics. These include Polyethylene Terephthalate (PETE), High-Density Polyethylene (HDPE), Polyvinyl Chloride (PVC), Low-Density Polyethylene (LDPE), Polypropylene (PP), Polystyrene (PS), and other variants such as Acrylonitrile Butadiene Styrene (ABS), Ethylene Vinyl Acetate (EVA), Polycarbonate (PC), and Polyurethane (PU). The focus is on their use in the construction of bituminous mixes via the dry process method. This method incorporates plastic waste into bituminous mixes by modifying the mixture or replacing aggregates. This practice has consistently demonstrated improvements in pavement performance, including increased stiffness, resistance to rutting, and fatigue. When bituminous mixtures are modified with the mixture modifying approach using low melting point plastics such as LDPE, HDPE, and LLDPE, a significant reduction in OBC is observed. Furthermore, the mixture modification approach has demonstrated higher resistance to moisture damage, rutting, and fatigue damage than the aggregate replacement approach. The potential benefits of using plastics in the bituminous pavement are substantial. This includes a reduction in the amount of waste sent to landfills, a decrease in reliance on finite natural resources, and the expansion of options for constructing bituminous pavements. Economic analyses have shown that using waste plastics can reduce pavement construction costs by 10%, with a minimal probability of leaching. Despite a multifold increase in the emission of greenhouse gases, an overall reduction in environmental impact was observed from the life cycle assessment study. However, the use of PVC and dark-colored plastics is not recommended. Field studies conducted on roads constructed with waste plastic-modified bituminous pavements showed notable improvements. Most of these pavements exhibited higher Pavement Condition Index (PCI) values and lower International Roughness Index (IRI) values than conventional pavements. These findings underscore the superior riding quality and reduced deterioration associated with waste plastic incorporation. Moreover, in-plant production processes, plants require minimal modifications, as existing equipment used for feeding fibers is well-suited for adding plastics into the mixture. In conclusion, further research is essential to fully understand the impact of different types of plastics on pavement performance and to evaluate this process's potential environmental and economic implications. This paper seeks to bridge the gap in the literature by reviewing and discussing the performance of such mixes and constructed pavements in laboratory and field situations. © 2024 Elsevier Ltd